2019
DOI: 10.1111/jfpe.13309
|View full text |Cite
|
Sign up to set email alerts
|

Parameters optimization and quality evaluation of mechanical properties of infrared radiation thin layer drying of pumpkin samples

Abstract: This work aims to estimate quality characteristics of dried pumpkin samples in an infrared dryer under natural and forced drying air convection systems. Drying time, rehydration ratio, and shrinkage as a function of infrared intensity, sample thickness, sample distance from the infrared lamps, and air velocity were optimized using response surface methodology. Maximum rehydration ratio and minimum drying time and shrinkage were assumed as criteria for optimizing drying conditions of the samples. The optimum va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The suitability of the quadratic model was evaluated using R 2 , adjusted‐ R 2 , predicted‐ R 2 , coefficient of variation (CV), and lack‐of‐fit of the model. Higher coefficient of determination ( R 2 ), the lesser difference between adjusted and predicted R 2 (<0.2), and adequate precision (>4) provide more adequacy (Sadeghi et al, 2020) to the regression equation which helps the model to predict the deviations during the drying. It is evident from Table 4 that the values of R 2 , adjusted‐ R 2 , and predicted‐ R 2 of all responses are high which represents a good relationship between the experimental and predicted values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suitability of the quadratic model was evaluated using R 2 , adjusted‐ R 2 , predicted‐ R 2 , coefficient of variation (CV), and lack‐of‐fit of the model. Higher coefficient of determination ( R 2 ), the lesser difference between adjusted and predicted R 2 (<0.2), and adequate precision (>4) provide more adequacy (Sadeghi et al, 2020) to the regression equation which helps the model to predict the deviations during the drying. It is evident from Table 4 that the values of R 2 , adjusted‐ R 2 , and predicted‐ R 2 of all responses are high which represents a good relationship between the experimental and predicted values.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in IRI up to 2,000 W/m 2 decreased the energy consumption initially because of the faster drying due to the high moisture removal rate from the product surface (Figure 6a,b). Increased SEC with an increase in IRI beyond the value of 2,000 W/m 2 can be attributed to the attainment of maximum drying rate and beyond which the additionally supplied IR SEC (Sadeghi et al, 2020). Similarly, a study on infrared convective drying of white mulberry fruit revealed that the AT had a positive effect on SEC, whereas the IR radiation was affected negatively.…”
Section: Effect Of Ir Intensity At and Ir Heat Source To Sample Dista...mentioning
confidence: 94%
“…This is mainly due to the higher mass transfer rate, which leads to a decrease in the RR. It is very likely to contribute to the acceleration of shrinkage due to the inability of the terebinth texture to maintain its network structure [ 42 ]. For drying savory leaves in an infrared–hot air dryer, Darvishi et al [ 6 ] showed that the highest RR was obtained at the lowest infrared power, while the lowest RR was obtained at the highest infrared power, which is consistent with the results of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have found that the level of infrared radiation temperature, the thickness of the slices, and the distance between the infrared radiation emitter and the sample surface affect the color, hardness and nutrient retention of the product during the infrared radiation drying process [5,30]. Based on the material characteristics of the cantaloupe slices and the preliminary experiments, the radiation temperature X 1 (55, 60 and 65 • C), slice thickness X 2 (5, 7 and 9 mm) and radiation distance X 3 (80, 120 and 160 mm) were the independent variables in this design.…”
Section: Experimental Designmentioning
confidence: 99%